Implementation of Universal Standards on General Disclo- Sure of Donowarih Village Sustainability Reports, Karangploso District, Malang District - Sukoharsono, Eko Ganis (Accounting Department, 2024)
Purpose: This study aims to describe the implementation of Universal Standards for Public Disclosure of Sustainability Reports in Donowarih Village, Karangploso District, Malang Regency. Method: The research employs a descriptive qualitative approach. It utilizes the existing standards in the Global Reporting Initiative (GRI) to measure the economic, social, and environmental dimensions of the indicators within the GRI framework. Findings: The study results indicate that the general disclosure of the sustainability report in Donowarih Village is currently well-implemented. Social and environmental reporting demonstrates the village's accountability actions concerning social and environmental aspects, encouraging all village officials to participate in sustainability reporting. Furthermore, regional autonomy in government appears highly effective in supporting the implementation of sustainable development based on concepts, programs, and strategies aligned with achieving sustainability reporting at the regional level. The implementation of the sustainability report signifies one way in which Donowarih Village is actively implementing the Sustainable Development Goals (SDGs). Practical Implications: This research provides valuable insights into the successful implementation of sustainability reporting at the village level. It can serve as a model for other villages and local governments in Indonesia to enhance their sustainability practices and reporting, ultimately contributing to broader national and global sustainability goals. Originality: While sustainability reporting in businesses is well-established, this study contributes to the literature by examining the implementation of such reporting at the village government level. This localized perspective offers a unique and valuable contribution to understanding sustainability practices within the context of local governance. Paper Type: This research can be classified as a case study within sustainability reporting and local governance.